“Найман арслант” хэмээх гүр дууньх өвөрлөгч нутаг дахь хэдэн хувилбарын тухай: Several variants of the gbr duu "Naiman Arslant" from the Övörlögch region - Б., Хишигсүх; Б., Хас-Эрдэнэ (Mongolian Studies, 2023)
The version of the religious song ’Naiman arslant’ [Eight lions/ has been still singing in Ordos Ikh-Zuu, Urad and Alagshaa. This song connects the nomadic people’s life to religion and worship. Marvel of four seasons in stanza expresses completely the features of Mongolians’ way of thinking.